Purchase order for supply, installation & commissioning of data centre electrical works with all necessary accessories for Brac University new campus project - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Edison Power Bangladesh Ltd. for supply, installation & commissioning of data centre electrical works with all necessary accessories for Brac University new campus project.